Bribery: Australian Managers’ Experiences and Responses When Operating in International Markets - Pedigo, Kerry L. (Journal of business ethics, 2009)
Managers seeking to respect local norms when operating in cross-cultural settings may encounter ethical dilemmas when faced with values that potentially conflict with their own. The question of whose ethics or values should be applied or whether a set of universal eth- ical norms should be developed often confronts managers in their international business dealings. This article explores the findings from a qualitative research study that examines critical ethical dilemmas confronting Australian managers in their international business operations and their responses to those dilemmas. For Australians managers in this study, bribery emerged as the major ethical dilemma confronting them in their international operations.